A Systematic Review about Semantic Description on the Internet of Things - Almeida, Henrique Gurgacz (2018)
The Internet of Things (IOT) is creating an ecosystem of objects connected on Internet. However, these objects are heterogeneous in terms of resources, characteristics, nature, protocols, actions and technologies. In this scenario, the Thing Description (TD) presents itself as an alternative to describe the IOT objects in a standard way and provide, among other possibilities, a better interoperability. Considering the rising research interest and the application opportunities of the TD, this paper presents a systematic review of the theme, aiming to identify applications, techniques, technologies and results using TD. 324 papers were identified and 46 were selected to be analyzed, which were classified in seven different groups of applications.